2019
DOI: 10.1136/bcr-2019-232065
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent leiomyoma of the vulva mimicking peripheral nerve sheath tumour

Abstract: Leiomyoma, a benign monoclonal tumour, is very rarely found in extrauterine sites, especially in the vulval region. Histopathology of the soft tissue tumours affecting this region is similar and immunohistochemistry (IHC) may be essential to confirm the diagnosis. We report a case of a 63-year-old postmenopausal woman who presented with a recurrent vulval mass involving the clitoris and left labia majora with suspected urethral involvement. Although the wedge biopsy was reported as peripheral nerve sheath tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Kothandaraman et al . reported a case of vulvar leiomyoma with recurrence after 4 years of primary excision [ 2 ]. Hence, the chances for recurrence and the need for regular long-term follow-up need to be explained to the patient [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kothandaraman et al . reported a case of vulvar leiomyoma with recurrence after 4 years of primary excision [ 2 ]. Hence, the chances for recurrence and the need for regular long-term follow-up need to be explained to the patient [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…On follow-up of these patients, only one patient with vulvar leiomyoma had recurrence after 10 years. Kothandaraman et al reported a case of vulvar leiomyoma with recurrence after 4 years of primary excision [2]. Hence, the chances for recurrence and the need for regular long-term follow-up need to be explained to ?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One case even died of a leiomyosarcoma of the vulva [ 17 ]. Therefore, it is recommended to surgically remove any vulval mass for proper histological and immunological examination [ [8] , [9] , [10] , [17] , [18] , [19] , [20] ]. This should be performed after proper ultrasonographic examination or even magnetic resonance imaging to determine preoperative soft tissue invasion [ 18 ] and to differentiate between a Bartholin gland cyst and a leiomyoma [ 7 ].…”
Section: Discussionmentioning
confidence: 99%